Research on the evaluation system of university data quality from the perspective of data elements - YANG Shuchun; WANG Yi (Tongxin xuebao)
In the digital era, data factor is a new production factor, its quality performance directly affects the performance of data factor. Based on the characteristics of informatization construction in colleges and universities, the dilemma of data quality in colleges and universities was deeply analyzed from the perspective of data elements, six attributes of data quality in colleges and universities were summarized and put forward, including completeness, uniqueness, accuracy, normalization, consistency and timeliness, and a data quality evaluation system was established in colleges and universities with business impact as the leading role from the business scenario. It is helpful for colleges and universities to carry out effective quality evaluation and accurate identification of problems on business data, and provide direction and basis for data governance in colleges and universities.